Ignoration of distortional co-ordinates in the theory of stability and control - Duncan, W. J. (College of Aeronautics, 1946)
Gates and Lyon have proposed to treat theoretically the stability and control of deformable aircraft by a method in which the distortion co-ordinates are ignored and the influence of distortion is allowed for by suitable modifications of the derivatives and other coefficients. in the 'present paper an exact method for eliminating the distortion co-ordinates is given and the conditions in which the true eliminant conforms with the simplification of Gates and Lyon are examined. In general the simplification is not justified mathematically, but in certain circumstances it provides an acceptable approximation. it will not be practically valid unless the structural distortions occur so relatively slowly that the associated inertia forces are negligible, i.e. the distortions must be quasi-static.